Business recovery and institutional constraints: evidence from Visegrad Countries and Serbia - Çera, Gentjan; Khan, Khurram Ajaz; Olah, Judit; Metzker, Zdenko (Journal of Business Economics and Management, 2023)
The current study investigates how institutional constraints and firms’ and entrepreneurs’ characteristics affect business recovery. Some elements have not yet been rigorously examined in the existing literature, especially not concerning the post-communist countries’ business recovery component and the same is the research gap current study intended to address. To evaluate the study model, ordinal logistic regression was used. More than 300 valid questionnaires are collected from the Czech Republic, Hungary, and Serbia. The findings show that factors such as firm tenure and size, location, sector, entrepreneurial motivation, product change, etc., have conflicting effects on business recovery. Some of the outcomes of the present study is supported by the existing studies and some requires further research. The study focuses on the less explored independent variables and their association with business recovery, specifically on SMEs, which highlights the paper’s originality. The output of the current study adds to the existing literature of business recovery and institutional constraints. Policymakers interested in removing institutional limitations and promoting a quicker business recovery for SMEs are drawn to the research. The study findings are also helpful from a managerial standpoint because business owners and managers significantly impact decisions about entrepreneur motivation, product change, and other issues.